A systematic review and meta-analysis of the prevalence of bipolar disorder among homeless people - Getinet Ayano; Shegaye Shumet; Getachew Tesfaw; Light Tsegay (BMC, 2020)
Abstract Background Bipolar disorder (BD) is a common severe mental disorder among homeless people and is associated with an increased risk of disability and mortality from suicide, medical causes (including HIV/AIDS, hepatitis infection, hypertension, and tuberculosis), as well as substance use disorders. However, a systematic synthesis of the existing evidence on the subject is lacking. To fill this gap in the literature, this study aimed to carry out systematic review and meta-analysis to determine the consolidated prevalence of BD among homeless people. Methods In this systematic review and meta-analysis, we searched Embase, PubMed, and Scopus to identify pertinent studies that reported the prevalence of BD among homeless people in March 2019. Random effect meta-analysis was employed to pool data from the eligible studies. Subgroup and sensitivity analysis was conducted and Cochran's Q- and the I2 test were utilized to quantify heterogeneity. Publication bias was assessed by using Egger's test and visual inspection of the symmetry in funnel plots. Results Of 3236 studies identified, 10 studies with 4300 homeless individuals were included in the final analysis. Among the 10 studies, five studies used the Diagnostic Statistical Manual of Mental disorders (DSM), three studies used Mini-International Neuropsychiatric Interview (MINI), one study used Schedule for Clinical Assessment of Neuropsychiatry (SCAN), and one study used Composite International Neuropsychiatric Interview (CIDI) to assess BD among homeless individuals. Based on the results of the random effect model, the prevalence of BD among homeless people was 11.4% (95% CI; 7.5-16.9). The prevalence of BD was 10.0% (95% CI; 3.1-27.9) in Europe and it was 13.2% (95% CI; 8.9-19.3) in other countries. Moreover, the prevalence of BD was 11.5% (95% CI; 5.5-22.3) for studies that used DSM to assess BD and it was 11.0% (95% CI; 6.1-19.2) for studies that used other instruments (MINI, SCAN, and CIDI). Conclusion Our meta-analysis demonstrated that BD is highly prevalent among homeless individuals, underlying the importance of early screening and targeted interventions for BD among homeless individuals.